2022
DOI: 10.1038/s42003-022-03700-6
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies to SARS-CoV-2 with a recurring YYDRxG motif retain binding and neutralization to variants of concern including Omicron

Abstract: Studying the antibody response to SARS-CoV-2 informs on how the human immune system can respond to antigenic variants as well as other SARS-related viruses. Here, we structurally identified a YYDRxG motif encoded by IGHD3-22 in CDR H3 that facilitates antibody targeting to a functionally conserved epitope on the SARS-CoV-2 receptor binding domain. A computational search for a YYDRxG pattern in publicly available sequences uncovered 100 such antibodies, many of which can neutralize SARS-CoV-2 variants and SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…In addition to mAbs targeting the RBS, COVA309-38 was found to target a more conserved cryptic site at the base and lateral face of the RBD. mAbs directed at this RBD region are generally broadly reactive but weakly neutralizing, although few exceptions exist like COVA1-16 6,49 and ADI-62113 51 . COVA1-16 exhibits a special angle of approach and is able to directly compete with the receptor binding through steric hindrance, thereby neutralizing SARS-CoV-2 much more potently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mAbs targeting the RBS, COVA309-38 was found to target a more conserved cryptic site at the base and lateral face of the RBD. mAbs directed at this RBD region are generally broadly reactive but weakly neutralizing, although few exceptions exist like COVA1-16 6,49 and ADI-62113 51 . COVA1-16 exhibits a special angle of approach and is able to directly compete with the receptor binding through steric hindrance, thereby neutralizing SARS-CoV-2 much more potently.…”
Section: Discussionmentioning
confidence: 99%
“…These three nanobodies bind the conserved epitope site previously described for CR3022 and COVA1-16 ( 41 , 42 ). Coincidently, these nanobodies bind SARS-CoV-2 RBD in a highly similar way as YYDRxG antibodies, e.g., COVA1-16 ( Bottom ) and ADI-62113 ( 43 ). ( F ) Nb-C4-225, Nb-C4-240, and Nb-C4-255 share similar CDRH3 motifs as COVA1-16.…”
Section: Resultsmentioning
confidence: 94%
“…Utilizing these sequences in the pursuit of a pancoronavirus vaccine could prove useful. A very recent study showed a conserved YYDRxG motif in the CDRH-3 region of antibodies predicts broad neutralizing activity (126). Neutralizing antibodies with a YYDrxG motif bind to a conserved epitope on the RBD of the spike protein (126).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study showed a conserved YYDRxG motif in the CDRH-3 region of antibodies predicts broad neutralizing activity (126). Neutralizing antibodies with a YYDrxG motif bind to a conserved epitope on the RBD of the spike protein (126). These results suggest that an epitope-targeted strategy to identify and isolate broadly neutralizing antibodies could also be fruitful.…”
Section: Discussionmentioning
confidence: 99%